Increasing the Competitiveness of Sweet Nutmeg and Papaya Products Owned by MSMEs in Cibeber Village, West Java Province, Indonesia - Alda Chairani; Pricilia Johani Sakti; Irfal Irfal; Eduard Rudolf Pangkerego (BASKARA : Journal of Business and Entrepreneurship, 2025)
This study aims to analyze strategies that can be applied to MSMEs producing candied nutmeg and papaya products in Cibeber Village to enhance their market competitiveness. A qualitative research method using in-depth interviews was conducted with 5 MSME actors and 5 regular consumers. The data collected was analyzed using SWOT analysis, with the Internal Factor Analysis Summary (IFAS) component to assess internal strengths and weaknesses, and the External Factor Analysis Summary (EFAS) to identify external opportunities and threats. The findings indicate that the most appropriate strategy is the ST (Strengths-Threats) strategy, which leverages internal strengths to address external threats such as intense competition and raw material price pressures. The novelty of this research lies in identifying the potential for MSMEs producing candied nutmeg and papaya to grow through improved packaging, product diversification, digital marketing, and more efficient supply chain management. The study recommends that MSMEs focus on utilizing technology for digital marketing, improving product quality, and expanding their market reach to mitigate external threats. Overall, this research offers new insights into marketing and product management strategies for local MSME development.